2016
DOI: 10.1139/cjps-2015-0331
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of cherry birch (Betula lentaL.)

Abstract: An efficient procedure for the micropropagation and conservation of cherry birch (Betula lenta L.), an endangered species in Canada, is reported. The model utilizes in vitro proliferation of fresh and dormant buds from both greenhouse and mature trees. Various factors were evaluated to optimize the protocol, including plant growth regulators, type and concentration of carbohydrates, and the composition of basal salts. 6-benzylaminopurine was the most effective cytokinin for shoot multiplication, with an optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…Agab & Greuter and Isoplexis isabiliana (Webb & Berth) Masf. [18,19,[32][33][34]. Stunted shoots at high concentrations of BA have also been observed in other plant species [35].…”
Section: Site Type Name Overwinter Survival (%) Flowering (%) Shoot Rmentioning
confidence: 95%
See 2 more Smart Citations
“…Agab & Greuter and Isoplexis isabiliana (Webb & Berth) Masf. [18,19,[32][33][34]. Stunted shoots at high concentrations of BA have also been observed in other plant species [35].…”
Section: Site Type Name Overwinter Survival (%) Flowering (%) Shoot Rmentioning
confidence: 95%
“…prevent species loss in the field. Earlier we developed micropropagation methods for several threatened North American plant species including American elm, cherry birch, and golden paintbrush [18,19,24,25]. The current study referred to as the CPR model was undertaken to assess the potential of micropropagated plants in establishing new plant populations in a range of diverse natural habitats.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Cultivation on MS medium has not been so successful (Ditmar 1991, Iliev et al 2003. On the contrary, Rathwell et al (2016) reported more promising results in Betula lenta cultures on MS and Driver and Kuniyuki Walnut medium (DKW -Driver & Kuniyuki 1984) as compared to WP medium. In our case, the shoots were vigorous and green on the control WP medium without BAP supply, but they grew less intensively, reaching just 2 and 4 mm after 4 and 8 weeks, respectively (Tab.…”
Section: In Vitro Culturementioning
confidence: 99%
“…Similarly, Máchová et al (2012) reported 98% success in ex vitro transfer in the case of B. nana. Rathwell et al (2016) reported that 110…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%